2020
DOI: 10.3389/fonc.2020.556489
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Stratification Based on a Novel Nomogram for Solitary Large Hepatocellular Carcinoma After Curative Resection

Abstract: Solitary large hepatocellular carcinoma (SLHCC) is a specific subtype of HCC with unique characteristics. It is of great interest to assess and stratify the prognosis of SLHCCs after curative resection. In this study, we tried to construct a prognostic nomogram for SLHCC following curative resection through a retrospective analysis of 202 SLHCC cases. Seven prognostic factors were identified and integrated to establish a novel prognostic nomogram, which included tumor size, microvascular invasion, tumor differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In addition, an intact capsule appearance observed by CT is indicative of a lower probability of MVI being present in the surrounding liver parenchyma (29,30). In this study, the multivariate analysis of AFP was adjusted for clinical variables for OS confirmed in previous reports (31,32). Notably, preoperative serum AFP may be an indirect indicator of tumor burden.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, an intact capsule appearance observed by CT is indicative of a lower probability of MVI being present in the surrounding liver parenchyma (29,30). In this study, the multivariate analysis of AFP was adjusted for clinical variables for OS confirmed in previous reports (31,32). Notably, preoperative serum AFP may be an indirect indicator of tumor burden.…”
Section: Discussionsupporting
confidence: 55%
“…Notably, preoperative serum AFP may be an indirect indicator of tumor burden. In fact, several studies have reported that an elevated AFP serum level is one of the crucial factors heralding poor survival after surgical resection, radiofrequency ablation, and transcatheter arterial chemoembolization of HCC (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence and survival after TACE in both groups are critical to the prognosis of patients. Zhuang et al (26) incorporated seven prognostic factors to construct a prognostic nomogram, and concluded that TACE combining with RFA was beneficial in patients with recurrent HCC in the low-risk group after LR, while TACE alone was sufficient for patients in the medium/high-risk group. Meanwhile, Lu et al (27) retrospectively analyzed clinical data from 597 HCC patients treated with TACE, suggesting that elevated platelet was associated with poor survival in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhuang et al. ( 26 ) incorporated seven prognostic factors to construct a prognostic nomogram, and concluded that TACE combining with RFA was beneficial in patients with recurrent HCC in the low-risk group after LR, while TACE alone was sufficient for patients in the medium/high-risk group. Meanwhile, Lu et al.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] The current literature showed that in carefully selected patients with huge HCC would benefit from liver resection as upfront treatment approach. 10,[26][27][28] Likewise, several comparative studies documented the superiority of liver resection for huge HCC compared with TACE regarding overall and recurrence-free survival. 1,29,30 Liver cirrhosis, the most common risk factor for development of HCC, was known to impair liver regeneration.…”
Section: Discussionmentioning
confidence: 99%